SISTEM Tata niaga KEDELAI DI DESA CIPEUYEUM, KECAMATAN HAURWANGI, KABUPATEN CIANJUR - Aldha Hermianty Alang; Heny Kuswanti Suwarsinah (Jurnal Manajemen & Agribisnis, 2013)
ABSTRACTThe objectives of this research were 1) identify the channel, institution, and trade system function of soy in Cipeuyeum Village, Haurwangi District, Cianjur, 2) Analyze the structure and the behavior of soy market in Cipeuyeum Village, Haurwangi District, Cianjur, also 3) Analyze the efficiency of soy trade system at each channel with trade channel margin approach, farmers’ share and profit-cost ratio (π/c). Qualitative and quantitative analysis were used to analyze the data. Qualitative analysis includes: channel and institution of the trade system, analysis of farmers and institutions functions involved in the trade system, analysis of market structure and behavior, trade system margin analysis, farmers’ share analysis, and analysis of π/c ratio.  There are four channels of marketing system in this village with five institutions that identified with the snowball method. The institutions within the trade systems perform their own function and face diverse market structures. Quantitative analysis showed that the most efficient channel is the one with Rp917 for the trade margin, 85,89% for the farmer’s share value, and 7,06 for profit-cost ratio. Therefore, Soybean Farmers should not sell the entire stock system directly to large traders without going through the small traders as it will increase the share of the farmers.Keywords: soy agribusiness, Cipeuyeum village, demand for soy, trade system of soy, soyABSTRAKTujuan dari penelitian ini adalah 1) mengidentifikasi saluran, lembaga, dan fungsi tata niaga kedelai di Desa Cipeuyeum, Kecamatan Haurwangi, Kabupaten Cianjur, 2) menganalisis struktur dan perilaku pasar kedelai di Desa Cipeuyeum, Kecamatan Haurwangi, Kabupaten Cianjur, dan 3) menganlisis efisiensi tata niaga kedelai pada setiap saluran yang ada dengan pendekatan margin tata niaga, farmer’s share, serta rasio keuntungan terhadap biaya (π/c). Analisis data dilakukan secara kualitatif dan kuantitatif. Analisis kualitatif  meliputi: saluran dan lembaga tata niaga, analisis fungsi tata niaga petani dan lembaga yang terlibat, analisis struktur dan perilaku pasar, Analisis margin tata niaga, analisis farmer’s share, dan analisis rasio π/c. Terdapat empat saluran tata niaga dengan lima lembaga yang diidentifikasi dengan metode snowball. Lembaga tata niaga ini masing-masing melakukan fungsi dan menghadapi struktur pasar yang beragam. Analisis kuantitatif menunjukkan satu saluran tata niaga yang paling efisien dengan margin sebesar Rp917 nilai farmer’s share sebesar 85,89%, dan rasio keuntungan terhadap biaya sebesar 7,06. Oleh karena itu, Petani sebaiknya melakukan penjualan kedelai tidak dengan sistem borong dan langsung kepada pedagang pengumpul besar tanpa melalui pedagang pengumpul kecil karena akan menambah share petani tersebutKata kunci: agribisnis kedelai, Desa Cipeuyeum, permintaan kedelai, tata niaga kedelai, kedelai